Usages des jeux video urbains dans le contexte de l'urbanisme participatif – le cas d'"INVESPACE-La Halle" (Rennes) - Marie-Anaïs Le Breton; Hélène Bailleul (Netcom)
The article deals with comparative use’s analysis of a hybrid urban video game developed by a French research unit (ESO) as part of an urban planning project in Rennes (France). Initially planned to analyse the involvement of young people in the city's factory, the INVESPACE-La Halle experiment also made it possible to observe professional representations of the gamification of co-design process. Finally, the article highlights the contributions and limitations of these digital experiments, on the one hand, in the development of participatory urban planning and, on the other hand, for research on participation.